(untitled) (Agroindustria, Sociedad y Ambiente, 2019)
The objective of the study was to evaluate the process of parbolizado and quality of the varieties of rice Payara 1FL and SD20A, coming from a commercial rice plant. The investigation was carried out in three stages: stage 1, the determination of the conditions of the parboiled at the laboratory level (soaking, steam cooking and drying); stage 2, determination of the mill performance of the parboiled and unbolted Payara 1FL and SD20A varieties, and stage 3, proximal analysis of the samples of white rice and parboiled rice processed in a company. The study is of the experimental field type and the results obtained were statistically analyzed, using the STATGRAPHICS program using a Variance Analysis. The study concluded that the optimal conditions for parboiling at the laboratory level were 20 hours of soaking at a temperature of 40 ° C, steam cooking for 35 minutes and drying at 45 ° C for 24 hours. Regarding the mill performance, it was for the SD20A variety of 58.78% and for the Payara 1FL 57.13% variety, both varieties showing good milling quality. For the proximal analysis, raw fiber values of 0.5 to 0.77%, fat 0.77 to 1.74%, ash 0.20 to 0.66%, protein 6.88 to 6.69% were obtained. , carbohydrates 80.45 to 78.64% and humidity 11.5% for the parboiled sample SD20A. In payara 1FL, the values obtained in crude fiber from 0.51 to 0.84%, in fat 0.41 to 1.14%, ash 0.21 to 0.53%, for protein 6.06 to 6.88 %, humidity 11.5% and carbohydrates 81.6 to 80.2%. Compared to white rice, there were significant differences due to the polishing process, it has lower amounts of nutrients. Demonstrating that the parboiling process allows better physical and chemical characteristics as well as the mill performance of the SD20A and Payara 1FL varieties.